Superconducting properties of a boson-exchange model of doped graphene - Loktev, V.M.; Turkowski, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
We study the superconducting properties of a doped one-layer graphene by using a model in which the interparticle attraction is caused by a boson (phonon-like) excitations. We study the dependencies of the superconducting gap D and the mean-field critical temperature TcMF on the carrier density, attraction strength and the characteristic (Debye) bosonic frequency. In addition, we study the temperature-carrier density phase diagram of the model by taking into account the thermal fluctuations of the order parameter. We show that the fluctuations result in a significant suppression of TcMF, such that the real (Berezinskii– Kosterlitz–Thouless) critical temperature Tc is much lower than TcMF. The region Tc < T < TcMF is characterized by a finite density of states at the Fermi level (the pseudogap phase). We show that the width of the temperature interval of the pseudogap phase strongly depends on the model parameters—carrier concentration, attraction amplitude, and boson frequency.